Bać się czy się nie bać? Bioakumulacja, bioindykacja i toksyczność metali ciężkich Rośliny w świetle badań terenowych i laboratoryjnych - Nadgórska-Socha, Aleksandra (Narracje o Zagładzie [czasopismo zamknięte], 2021)
Heavy metals that pose a threat to the environment include lead (Pb), zinc (Zn), copper (Cu), arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni) and mercury (Hg). Biomonitoring of environmental quality using plants is widely accepted as a reliable and inexpensive way of obtaining information on contamination also by heavy metals. It allows the assessment of the direction of changes in the natural environment and development of prognoses and methods for early warning related to predicted transformations in ecosystems. This paper presents the results of field and laboratory studies on floristic biodiversity in the areas of southern Poland related to extraction and processing of Zn and Pb ores. The paper also shows the selected plant defence mechanisms against the excess of heavy metals and the results of bioindication studies using different plant species, including the selected metallophytes related to the assessment of contamination levels and the most frequently used plant ecophysiological parameters. It is necessary to monitor contamination level, popularize knowledge and take action at the level of local authorities to mitigate adverse effects of human activity, bearing in mind possible bioaccumulation of heavy metals in the food chain and the adverse health effects associated with environmental contamination.